2023
DOI: 10.1136/ard-2023-224575
|View full text |Cite
|
Sign up to set email alerts
|

The 2023 ACR/EULAR classification criteria for calcium pyrophosphate deposition disease

Abstract: ObjectiveCalcium pyrophosphate deposition (CPPD) disease is prevalent and has diverse presentations, but there are no validated classification criteria for this symptomatic arthritis. The American College of Rheumatology (ACR) and EULAR have developed the first-ever validated classification criteria for symptomatic CPPD disease.MethodsSupported by the ACR and EULAR, a multinational group of investigators followed established methodology to develop these disease classification criteria. The group generated list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
11
0
4
Order By: Relevance
“…Die detaillierte Beschreibung der Entwicklung der Klassifikationskriterien für die CPPD-Erkrankung ist der Originalpublikation zu entnehmen (Abb. 5 ; [ 16 , 17 ]). Diese gliederte sich in die Erstellung von Variablenlisten, die Identifikation von Patientenprofilen und die Untersuchung der Assoziationen zwischen den Variablen und der CPPD-Erkrankung.…”
Section: Methodenunclassified
See 2 more Smart Citations
“…Die detaillierte Beschreibung der Entwicklung der Klassifikationskriterien für die CPPD-Erkrankung ist der Originalpublikation zu entnehmen (Abb. 5 ; [ 16 , 17 ]). Diese gliederte sich in die Erstellung von Variablenlisten, die Identifikation von Patientenprofilen und die Untersuchung der Assoziationen zwischen den Variablen und der CPPD-Erkrankung.…”
Section: Methodenunclassified
“…Liegen diese Befunde nicht vor, kann eine Punktzahl von mehr als 56 Punkten anhand gewichteter Kriterien, die sich aus klinischen Merkmalen, begleitenden Stoffwechselstörungen und Ergebnissen von Labor- und Bildgebungsuntersuchungen zusammensetzen, zur Klassifikation als CPPD-Erkrankung herangezogen werden. Diese Kriterien hatten eine Sensitivität von 92,2 % und eine Spezifität von 87,9 % in der Entwicklungskohorte (190 CPPD-Fälle, 148 CPPD „mimics“), während die Sensitivität 99,2 % und die Spezifität 92,5 % in der Validierungskohorte (251 CPPD-Fälle, 162 CPPD „mimics“) betrug ([ 17 ]; s. auch Abb. 6 ).…”
Section: Ergebnisseunclassified
See 1 more Smart Citation
“…Finally, the 2023 EULAR/ACR classification criteria for CPPD disease, categorized CPPD patients in three clinical phenotypes based on the number and course of clinical symptoms. These phenotypes emerged by the preliminary collection of a large number of clinical cases and after the statistical analysis was performed, the phenotype ‘more than one attacks of acute arthritis’ appeared to be the most specific one for CPPD while ‘persistent arthritis’ the least as deduced from their weight in the classification items [8 ▪▪ ].…”
Section: Describing Calcium Pyrophosphate Deposition By Nomenclature:...mentioning
confidence: 99%
“…However, should be kept in mind that a significant limitation in describing CPPD by radiography lies in its two-dimensional nature, where the superimposition of different structures, especially in case of advance osteoarthritis, can affect the recognition of CPP deposits [35]. Indeed, recent studies have confirmed that the sensitivity of radiography for CPPD identification is far from being optimal, but thanks to its high specificity, detecting CPPD on radiography is considered at the same level as ultrasound and CT in the recently published classification criteria for CPPD disease [8 ▪▪ ,9 ▪▪ ]. The development of a radiographic scoring system for CPPD extent in the near future, could contribute further to enhancing the role of radiography in characterization of CPPD.…”
Section: Describing Calcium Pyrophosphate Deposition Through Imagingmentioning
confidence: 99%